Pengembangan Bahan Ajar Pada Materi Kesultanan Siak Di Bawah Pemerintahan Hindia Belanda (1713-1864) Pada Mata Pelajaran Sejarah Peminatan - Yullia, Lela (Krinok: Jurnal Pendidikan Sejarah dan Sejarah, 2024)
The Sultanate of Siak is one of the areas that cannot be separated from the cultivation of Dutch Colonialism in 1713-1864. This research was conducted to identify how the development of the Siak Sultanate in western influence, especially Dutch Colonialism in the Siak Sultanate, which can be used as a source of learning, especially the development of teaching materials in historical subjects of specialization, especially during the period of Dutch Colonialism. This research method uses descriptive qualitative research. The results showed that the Siak Sultanate during colonialism could be used as the development of teaching materials in the History subject of specialization. The development of history teaching materials in the History subject of specialization is very useful for students because the material is close to their living environment, thus making the goals of learning history achieved and becoming more meaningful. In addition, it can also build the character of love for history and the nature of responsibility for sustainability, concern for heritage and historical heritage and foster a sense of nationalism.